Educational electrolyzer prototype: Improving engineering students' knowledge in renewable energies - de Almeida Rezende, Lucas [UNESP]; de Campos, Victor Arruda Ferraz [UNESP]; Silveira, José Luz [UNESP]; Tuna, Celso Eduardo [UNESP] (Elsevier, 2021)
This article aims to demonstrate the process of building a low-cost water electrolyzer using common materials and to analyze the influence of practical experiments on students' knowledge. Practical classroom experiments are of great importance to students' learning and problems such as bureaucracy in the teaching department, high cost of equipment and lack of teacher time are some of the factors responsible for the delay in performing them in the classroom. Applying the Advanced Product Quality Planning methodology, Active Learning, thermodynamic and electrochemical modeling, it was possible to build an electrolyzer with about 150 US$. In the electrolyzer, the electrolytic solutions with 1 M concentration of NaOH and KOH were used, i.e., 39 g L−1 and 64 g L−1, respectively, to produce the gases hydrogen and oxygen. The flow of hydrogen and oxygen for the KOH electrolytic solution was 1.22 L min−1 and for the NaOH solution, 1.07 L min−1 was found using a 9–12 V and 8–15 A adjustable transformer. Among the undergraduate students who were interviewed, 54% did not know electrolysis and 46% knew just the basic concepts. After the practical experiment, it was observed that 94% of the students understood the concepts of the electrochemical reaction. Based on the averages of the two tests applied to students, before and after the practical experiment, an increase of 58% in the correctness of the questions was found for students who had not heard of electrolysis before and a 13% increase was observed for those who already knew the basic concepts. With this experiment, it was possible to observe how much practical activities in the classroom can positively influence the understanding of electrolysis and make students aware of this renewable energy production process.
Keywords: Active learning; Electrolysis; Hydrogen electrolyzer; Renewable energy